2008
DOI: 10.1063/1.2973988
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-induced light scattering for improved performance of quantum-well solar cells

Abstract: We report on the improved performance of InP / InGaAsP quantum-well waveguide solar cells via light scattering from deposited dielectric or metal nanoparticles. The integration of metal or dielectric nanoparticles above the quantum-well solar cell device is shown to couple normally incident light into lateral optical propagation paths, with optical confinement provided by the refractive index contrast between the quantum-well layers and surrounding material. With minimal optimization, short-circuit current den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 19 publications
2
88
0
1
Order By: Relevance
“…They have also observed that the dense nanoparticles further improved both electrical and optical properties of the GaN MSM UV PDs. Derkacs et al 19 also utilized SiO 2 nanoparticles for improving optical absorption efficiency in GaAs based solar cell. …”
Section: Resultsmentioning
confidence: 99%
“…They have also observed that the dense nanoparticles further improved both electrical and optical properties of the GaN MSM UV PDs. Derkacs et al 19 also utilized SiO 2 nanoparticles for improving optical absorption efficiency in GaAs based solar cell. …”
Section: Resultsmentioning
confidence: 99%
“…Для одночасної електронної ре-єстрації величини оптичного пропускання та візуального спостере-ження процесів утворення кластерів магнетних частинок, лазерний промінь, що виходив з електромагнету, розділявся на два пучки променів за допомогою світлорозділювального елемента -пластин-ки або призми (4). Один із таких пучків фокусувався на фотоприй-мачеві (5), а інший -на CMOS камері (6). За допомогою модуля ре-єстрації напруги Triton 3000U, що був приєднаний до фотоприйма-ча, вдавалося проводити виміри з часовою роздільною здатністю 150 мс.…”
Section: методика та умови експериментуunclassified
“…Light scattering Silicon and Gold Nanoparticle shown improved performance of quantumwell solar cells with a 17% power conversion efficiency (Derkacs et al 2008). 94% of the light can absorb by 280 nm thick hydrogenated amorphous silicon (A-Si:h) layer in nano dome based solar cell.…”
Section: Developments Of Solar Cell Using Quantum Dots (Qds)mentioning
confidence: 99%